THE EFFECTS OF HYPERVELOCITY IMPACT ON CRYSTALLINE ROCKS FROM THE HAUGHTON IMPACT STRUCTURE, DEVON ISLAND, CANADA - Singleton, Alaura C. (Scholarship@Western, 2010)
The Earth is constantly being struck by objects from space, which can create enormous pressures and temperatures on a limited area over a very short period of time creating conditions unlike those created by any other geological process. The resulting â€œshockâ€ metamorphism can occur at pressures that reach hundreds of GigaPascals and well over a thousand degrees Kelvin altering the target material on both megascopic and microscopic scales. Much remains to be understood regarding effects at small length scales such as the degree to which vaporization and melting create porosity in target rocks, and the nature of distinctive microfeatures in accessory geochronology minerals such as zircon (ZrSiO4). This thesis explores the effects of shock metamorphism on crystalline, quartzofeldspathic basement material from the ~39 million year old Haughton impact structure on Devon Island, selected because of its high degree of preservation of shock assemblages. This thesis consists of three main lines of research. One main portion of this study involved assigning shock levels to these samples based on petrographic examination of * main mineral phases and conventional shock classification schemes, and a classification system created for this project. A total of 52 crystalline bedrock samples from a breccia unit in the crater, and one reference site outside of the crater, were classified using this system. The shock levels determined in this way range from 0 to 7 indicating shock pressures ranging from 2 to 80 GPa at the time of the impact which agrees with previously published estimates for Haughton samples. The second main line of research involved measuring physical characteristics (e.g. density and porosity) of the shocked samples to discover how these relate to the assigned shock levels. The bulk density, grain density, and porosity of a wide range of samples were determined using a water displacement method, a bead displacement method, and analysis using a He-pycnometer. Results suggest a nonlinear, negative correlation ...